Development of a Highly Efficient Hybrid Peptide That Increases Immunomodulatory Activity Via the TLR4-Mediated Nuclear Factor-κB Signaling Pathway - Zhang, Lulu (Int J Mol Sci, 2019)
Immunity is a defensive response that fights disease by identifying and destroying harmful substances or microbiological toxins. Several factors, including work-related stress, pollution, and immunosuppressive agents, contribute to low immunity and poor health. Native peptides, a new class of immunoregulatory agents, have the potential for treating immunodeficiencies, malignancies, and infections. However, the potential cytotoxicity and low immunoregulatory activity and stability of native peptides have prevented their development. Therefore, we designed three hybrid peptides (LTA(a), LTA(b), and LTA(c)) by combining a characteristic fragment of LL-37 with an active Tα1 center that included Tα1 (17–24), Tα1 (20–25), and Tα1 (20–27). The best hybrid peptide (LTA(a)), according to molecule docking and in vitro experiments, had improved immunoregulatory activity and stability with minimal cytotoxicity. We investigated the immunoregulatory effects and mechanisms of LTA(a) using a cyclophosphamide-immunosuppressed murine model. LTA(a) effectively reversed immunosuppression by enhancing immune organ development, activating peritoneal macrophage phagocytosis, regulating T lymphocyte subsets, and increasing cytokine (tumor necrosis factor-alpha, interleukin-6, and interleukin-1β) and immunoglobulin (IgA, IgG, and IgM) contents. The immunomodulatory effects of LTA(a) may be associated with binding to the TLR4/MD-2 complex and activation of the NF-κB signaling pathway. Therefore, LTA(a) could be an effective therapeutic agent for improving immune function.